The Management of Urticaria Pigmentosa: A Literature Review - Pujiastuti, Agustina Tri (Journal of Diverse Medical Research: Medicosphere, 2024)
ABSTRACT Background: Urticaria pigmentosum is the most common skin manifestation of cutaneous mastocytosis. This disease has similarity with others, therefor misdiagnose is common occurrence. Methods. Literature searching was conducted using databases such as PubMed, Google Scholar, and Web of Science using Search terms included "urticaria," "mastocytosis," "treatment," and "mast cell.". Systematic reviews of peer-reviewed articles, reports, and case studies were chosen. Discussion: The management of urticaria pigmentosa consists of three lines of therapy, which can be utilized based on each patient’s response. Conclusion: The proper management of urticaria pigmentosum is important to eliminate symptoms and improve the patient’s quality of life.   Key words: Urticaria pigmentosum, mastocytosis, management